THE EFFECTIVENESS OF USING GOOGLE CLASSROOM IN IMPROVING STUDENT LEARNING OUTCOMES IN ENTREPRENEURSHIP COURSES - Widoretno, Yustin Setiya; Umaroh, Susi Tri (STKIP PGRI Tulungagung, 2025)
The rapid advancement of science and technology has transformed education, necessitating effective digital learning tools like Google Classroom, particularly during the COVID-19 pandemic. While previous studies have explored its general educational benefits, its specific effec-tiveness in vocational technical education—particularly for Entrepre-neurship courses in engineering programs—remains under-researched. This study addresses that gap by quantitatively assessing Google Class-room’s impact on 45 D4 Mechanical Engineering students at Universi-tas Negeri Surabaya. Results show that 44% of respondents strongly agree on the platform’s usability and flexibility, while 50% confirm its role in enhancing comprehension, assignment completion, and academ-ic performance in Entrepreneurship. Statistical analysis further validates these findings, with a significant t-test result (t-count = 2.365 > t-table = 2.025) demonstrating improved learning outcomes. By providing empir-ical evidence of Google Classroom’s efficacy in a vocational engineer-ing context, this study contributes novel insights to digital pedagogy literature. The findings advocate for the platform’s broader adoption in technical higher education, supporting optimized digital learning strate-gies in the industry 4.0 era.